2017
DOI: 10.1590/0103-11042017s18
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Programa de Controle da Tuberculose: um estudo de caso

Abstract: RESUMO A falta de integração entre os serviços que compõem a rede de atenção à saúde, além da incapacidade de muitos profissionais, são apontadas como causas da problemática para o controle da tuberculose no Brasil. Este estudo avaliou o grau de implantação do Programa de Controle de Tuberculose (PCT) em Divinópolis (MG). Trata-se de uma pesquisa avaliativa na perspectiva de análise de implantação. O PCT encontra-se parcialmente implantado. Como limitações, destacam-se a deficiência de gestão e planejamento, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
23

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 14 publications
1
23
0
23
Order By: Relevance
“…The results of a study conducted in Divinópolis, Minas Gerais, demonstrated that the local TB control program had as difficulties: a fragile planning process, lack of a standard model for the diffusion of information and data, lack of a training program and trained professionals, who in turn, demonstrated lack of knowledge in diverse areas such as surveillance, TB diagnosis, and accomplishing the DOT 16 . In Cabedelo, Paraíba, other factors emerged as barriers in the management and performance of primary care services in relation to TB treatment, such as: the fragmentation of professional practice, lack of systematization in home care, and focus of the professional qualification 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study conducted in Divinópolis, Minas Gerais, demonstrated that the local TB control program had as difficulties: a fragile planning process, lack of a standard model for the diffusion of information and data, lack of a training program and trained professionals, who in turn, demonstrated lack of knowledge in diverse areas such as surveillance, TB diagnosis, and accomplishing the DOT 16 . In Cabedelo, Paraíba, other factors emerged as barriers in the management and performance of primary care services in relation to TB treatment, such as: the fragmentation of professional practice, lack of systematization in home care, and focus of the professional qualification 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The National Tuberculosis Control Program in Brazil, seeks to improve the qualification of processes such as planning, monitoring, evaluation of control actions, prevention, care, diagnosis, epidemiological surveillance, etc 16 . A study conducted in the Tak province, Thailand, demonstrated that planning, was one of the main elements for disease control in that setting, along with effective sharing of data and information, and improvement in the diagnosis process and care, among others things 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Outro ponto importante é a análise que se refere à organização do trabalho, onde durante a coleta de dados, foi visto que ocorre de maneira fragmentada, onde as atividades são restritas à determinadas categorias profissionais. Este fato foi também identificado em estudo que apontou fragmentação das atividades entre os profissionais, dificuldades em lidar com as pessoas com TB, assim como no manejo clínico 16 .…”
Section: Resultsunclassified
“…Não se pode afirmar como tal questão influencia na adesão de homens e mulheres ao tratamento da tuberculose, entretanto, reafirma-se realidade condicionada socialmente ao gênero (Kergoat, 1996;Toledo, 2008;Biroli, 2014;Herrero et al, 2015). (Bertolozzi, 2005;Andrade et al, 2017;PERI et al, 2018).…”
Section: I S C U S S ã O | 141unclassified
“…É um elemento facilitador para a adesão ao tratamento, pois constitui-se em uma ferramenta de vínculo entre o profissional e o paciente, possibilitando a autonomia e a emancipação do sujeito portador da doença, de maneira com que ele/ela se sinta corresponsável pelo tratamento. Muitos estudos têm demonstrado a eficácia dessa modalidade de tratamento em relação à adesão, corroborado os resultados do presente estudo (Bertolozzi, 2005;Queiroz, Nogueira, 2010;Sá et al, 2012;Andrade et al,2017;Furlan, Santos Junior, Marcon, 2017;Pinheiro et al, 2017;Diallo et al, 2018;Gyiman,Dako-Gyeke, 2019).…”
Section: I S C U S S ã O | 158unclassified